A new species of Principiala (Ithonidae) from the Lower Cretaceous Sinuiju Formation, Democratic People's Republic of Korea. (June 2023) - Won, Chol-Guk; Ri, Song; Ri, Chol-Jun; So, Kwang-Sik
Abstract: A new fossil species, Principiala sinuijuensis sp. nov. (Ithonidae), collected from the Lower Cretaceous Sinuiju Formation, North Phyongan Province, has the following forewing characters: Humeral veinlet recurrent arcuately curved; many ra–rp crossveins; MA short, proximal 5 branches of RP fused with MA; MP forking close to wing base, proximally with 4 mp1–mp2 crossveins; the posterior branch of MP fused with the anterior primary branch of CuA at midpoint of wing. The well preserved material not only expands our knowledge of the morphology of Ithonidae and the geographic distribution of Principiala but also increases the diversity of the Early Cretaceous lacewings in the Sinuiju Biota. Highlights: Second fossil Ithonid was collected from the Lower Cretaceous, DPRK. It is Principiala sinuijuensis sp. nov. It offers us a chance to study and better understand Mesozoic Ithonidae.